2010
DOI: 10.1371/journal.pone.0012591
|View full text |Cite
|
Sign up to set email alerts
|

Reassortant between Human-Like H3N2 and Avian H5 Subtype Influenza A Viruses in Pigs: A Potential Public Health Risk

Abstract: BackgroundHuman-like H3N2 influenza viruses have repeatedly been transmitted to domestic pigs in different regions of the world, but it is still uncertain whether any of these variants could become established in pig populations. The fact that different subtypes of influenza viruses have been detected in pigs makes them an ideal candidate for the genesis of a possible reassortant virus with both human and avian origins. However, the determination of whether pigs can act as a “mixing vessel” for a possible futu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 45 publications
0
16
0
1
Order By: Relevance
“…Experimental studies have demonstrated influenza reassortment using pigs as a mixing vessel 8, 9. Furthermore, genetic‐based surveillance and epidemiologic reports have highlighted natural reassortment events within a narrow time frame, location, and likely group of pigs 10, 11, 12…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies have demonstrated influenza reassortment using pigs as a mixing vessel 8, 9. Furthermore, genetic‐based surveillance and epidemiologic reports have highlighted natural reassortment events within a narrow time frame, location, and likely group of pigs 10, 11, 12…”
Section: Introductionmentioning
confidence: 99%
“…The ongoing risk that viral reassortment poses was highlighted by the emergence of the 2009 triple reassortant swine-origin H1N1 pandemic virus [6]. Furthermore, the highly pathogenic H5N1 avian influenza virus has recently crossed the species barrier to infect humans resulting in a high mortality rate, and reassortant viruses with internal genes of avian H5 lineage have been identified in swine, raising concern about the pandemic potential of reassortant H5 viruses [7,8]. …”
Section: Introductionmentioning
confidence: 99%
“…Similarly, RGd-RV with the HA gene from H5N1 virus in the H1N1pdm2009 genetic background replicated efficiently in primary human respiratory epithelial cells and caused 100% mortality in mice (19). However, phylogenetic analyses of natural or experimental reassortant viruses have shown that the HA segment from avian, swine, or equine viruses was never incorporated alone in the genetic background of a human virus (13,14,20): The HA segment is packaged with additional groups of gene segments depending on the viral subtypes involved in the coinfection process (13,14).The inability to obtain a virus containing a nonhuman HA gene in an otherwise human genetic background, in contrast with the ability to produce "7+1" RGd-RV with a high yield of replication, suggests that the reassortment process might be restricted by suboptimal compatibility between the vRNA-packaging signals (10).…”
mentioning
confidence: 99%